1893
DOI: 10.1080/00378941.1893.10828818
|View full text |Cite
|
Sign up to set email alerts
|

Nouvelles Observations Sur La Membrane

Abstract: 273de la répétition des parties homologues, comme aussi, ce que nous développerons ailleurs, avec la signification de la variété et de la localisation des organes.De tout ce qui précède ressort, démontrée, cette proposition : La mu·ttiplicité des organes homologues est un signe d'abaissement dans tes végétaux.Or cette proposition, établie sur des faits empruntés exclusivement aux plantes, on peut l'appuyer indirectement sur le règne animal, soit qu'on considère certains animaux aux divers stades de leur évolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Plant biologists soon recognized that pectins were the main components in the middle lamella between cells and were also present in the PCW, along with cellulose, hemicelluloses, and to a lesser extent lignin ( Mangin 1893a , 1893b ; Kerr and Bailey 1934 ). Some, including Mangin (1893b) and Bonner (1936) , suggested that pectins in the middle lamella existed as calcium pectate, whereas others concluded that they existed as “protopectin” and/or a pectin-protein complex ( Sloep 1928 ; Kertesz 1951 ).…”
Section: The 5 Major Polymers Of the Plant Cell Wallmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant biologists soon recognized that pectins were the main components in the middle lamella between cells and were also present in the PCW, along with cellulose, hemicelluloses, and to a lesser extent lignin ( Mangin 1893a , 1893b ; Kerr and Bailey 1934 ). Some, including Mangin (1893b) and Bonner (1936) , suggested that pectins in the middle lamella existed as calcium pectate, whereas others concluded that they existed as “protopectin” and/or a pectin-protein complex ( Sloep 1928 ; Kertesz 1951 ).…”
Section: The 5 Major Polymers Of the Plant Cell Wallmentioning
confidence: 99%
“…Plant biologists soon recognized that pectins were the main components in the middle lamella between cells and were also present in the PCW, along with cellulose, hemicelluloses, and to a lesser extent lignin ( Mangin 1893a , 1893b ; Kerr and Bailey 1934 ). Some, including Mangin (1893b) and Bonner (1936) , suggested that pectins in the middle lamella existed as calcium pectate, whereas others concluded that they existed as “protopectin” and/or a pectin-protein complex ( Sloep 1928 ; Kertesz 1951 ). More recent results with antibodies recognizing RG-I ( Moore and Staehelin 1988 ) and transgenic plants expressing reduced levels of pectin metabolic enzymes clearly show that the pectin in the middle lamella contains not only HG but also RG-I ( Molina-Hidalgo et al 2013 ).…”
Section: The 5 Major Polymers Of the Plant Cell Wallmentioning
confidence: 99%
“…The cyst mucilage, which could be attached to young cysts, contained sulphur and silica [ 161 ]. In addition to dinosporin, the young resting cyst wall was purported to contain, based on histochemical interpretations, cellulose (internal), pectic compounds (pectin, exterior), and callose (which appeared later and was possibly associated with germination) [ 32 , 162 ].…”
Section: Development Of Resting Cysts Amphiesmamentioning
confidence: 99%